2006
DOI: 10.1016/j.bbabio.2006.02.011
|View full text |Cite
|
Sign up to set email alerts
|

A functionally inactive, cold-stabilized form of the Escherichia coli F1Fo ATP synthase

Abstract: An unusual effect of temperature on the ATPase activity of E. coli F1Fo ATP synthase has been investigated. The rate of ATP hydrolysis by the isolated enzyme, previously kept on ice, showed a lag phase when measured at 15 degrees C, but not at 37 degrees C. A pre-incubation of the enzyme at room temperature for 5 min completely eliminated the lag phase, and resulted in a higher steady-state rate. Similar results were obtained using the isolated enzyme after incorporation into liposomes. The initial rates of AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Representative traces are shown. Similar results have been obtained using a luciferase assay (Galkin et al 2006)…”
Section: Figsupporting
confidence: 85%
See 1 more Smart Citation
“…Representative traces are shown. Similar results have been obtained using a luciferase assay (Galkin et al 2006)…”
Section: Figsupporting
confidence: 85%
“…ATP synthesis by membranes was measured with pH-indicator phenol red at 37°C following scalar proton consumption at 557 nm. Membranes were prepared as described in (Galkin et al 2006; Ishmukhametov et al 2008). Reactions were initiated by adding 20 mM succinate to a 2 ml cuvette containing 200 μg membrane protein in 10 mM phosphate (potassium salts) at pH 8.0, 100 mM KCl, 5 mM MgCl 2 , 0,1 mM EDTA, 0.7 mM ADP.…”
Section: Methodsmentioning
confidence: 99%
“…F 1 F o -ATPase was purified from E. coli strain DK8 harboring plasmid pFV2, as previously described. Growth of cultures, preparation of membrane vesicles, purification of F 1 F o , and reconstitution into liposomes were also carried out as described previously [20,22]. Succinate minimal medium was made from minimal medium A [23], supplemented with 0.2% succinic acid (from a stock adjusted to pH 6.4 with KOH), and 0.2 mM L-valine, L-leucine and L-isoleucine.…”
Section: Plasmids Mutagenesis Growth and Expressionmentioning
confidence: 99%
“…For pH dependence ACMA-fluorescence quenching, the buffer was 5mM Tris/ 5 mM maleate, supplemented with 15 μM valinomycin. ATP synthesis was carried out using a luciferase assay as described previously [22]. Prior to measurement of ATP synthesis, membrane vesicles were resuspended in 1 ml of buffer (200 mM Tricine/HCl, pH 7.8, 100 mM KCl, 5 mM MgCl2, and 2.5% glycerol), passed through a 10-ml Sephadex G-50 column, equilibrated with the same buffer.…”
Section: Functional Assaysmentioning
confidence: 99%
“…The uncF (b subunit) genes in these plasmids retained the designed chimeric b subunit gene and carried no other mutations. A recent publication suggested that a cold-stabilized form of the complex had a significant lag in ATP hydrolysis activity (12). Therefore, ATP hydrolysis was carefully reexamined under conditions that would account for a potential lag, and results essentially identical to those shown in Table 3 were obtained.…”
Section: Resultsmentioning
confidence: 93%